METODE SYARH HADIS: METODE FIQH, TEKNIK INTERPRETASI DAN PENDEKATAN DALAM MEMAHAMI HADIS - Darul, Muhammad Ghalib (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The Methodology of Syarh Hadith: A Study of Interpretive Methods and Approaches Syarh hadith refers to the science of explaining the authenticity and potential flaws in the matn (text) and sanad (chain of transmission) of hadiths, interpreting their meanings, and deriving legal rulings and moral wisdoms from them. This study aims to explore the methodology of syarh hadith, including the methods of fiqh al-hadith, interpretive techniques, and the various approaches used in understanding the sayings of the Prophet Muhammad (peace be upon him) both textually and contextually. The research adopts a qualitative approach through library research, utilizing primary sources from classical and contemporary works of syarh hadith, and secondary data from relevant academic journals. Data collection was conducted by tracing, reading, note-taking, and classifying information, which was then analyzed using a descriptive-analytical method. The findings of this study reveal that the primary methods of syarh hadith include taḥlili (analytical), ijmali (comprehensive or summary), muqaran (comparative), and mauḍu‘i (thematic) methods. The fiqh al-hadith methodology is divided into two main approaches: textual and contextual. The interpretive techniques employed in syarh hadith encompass linguistic, historical, scientific, interdisciplinary, and multidisciplinary approaches. This research emphasizes that mastery of these methods and approaches is crucial for maintaining the authenticity of the Prophet’s sayings and preventing misinterpretations in the practice of Islamic teachings in modern society.